Influence of helium induced nanostructures on the thermal shock performance of tungsten. (December 2016) - Wirtz, M.; Berger, M.; Huber, A.; Kreter, A.; Linke, J.; Pintsuk, G.; Rasinski, M.; Sergienko, G.; Unterberg, B.
Highlights: Combined steady-state He-plasma and thermal shock exposure of W. Strong modification of the W-fuzz, if combined with thermal shocks. He induced nanostructures grow in cracks and enhance the risk of erosion. Formation of He-bubbles near the surface reduces the thermal conductivity. Alteration of laser absorption due to W-fuzz influences the thermal shock behavior. Abstract: Experiments were performed in the linear plasma device PSI-2 in order to investigate the synergistic effects of combined steady-state He-plasma and thermal shock exposure. Tungsten produced according to the ITER material specifications by Plansee SE, Austria, was loaded sequentially and simultaneously by steady-state He plasma and transient thermal loads induced by a laser beam. All tungsten samples were exposed to helium plasma for 40 min at a base temperature of ca. 850 °C and a flux of ca. 2.8 × 10 22 m −2 s −1 . Before, during and after the plasma exposure 1000 thermal shock pulses with a pulse duration of 1 ms and a power density 0.76 GW/m² were applied on the samples. The thermal shock exposure before and after plasma exposure was done at room temperature in order to investigate helium induced surface effects also within cracks. The obtained results show that the combination of He plasma with transient thermal shock events results in a severe modification such as reduced height or agglomeration of the sub-surface He-bubbles and of the created nanostructures, i.e. W-fuzz.